Performance of Implementation Program Keluarga Harapan in Jember Regency - Altatur, Aulia Kamal Altatur (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2024)
Public programs must be managed with the aim of achieving desired results. As a poverty alleviation program that has been running in Indonesia, the Program Keluarga Harapan (PKH) has a policy direction not only to ensure that assistance is right on target but also to eradicate poverty with the target result being empowered and prosperous. A study of program implementation performance can describe the failure or success of implementing a policy. This research aims to analyze the performance of the implementation of the PKH in Jember Regency. Analysis using the performance measurement framework by Cole and Parston (2006) includes policy input, processes, policy output, and policy outcome policy. Then, assess the quality of policy output using policy output aspects from Randall B. Ripley including access, coverage, frequency, bias, timeliness of services, accountability, and suitability of programs to needs. The research method used is a descriptive qualitative approach. Data analysis uses interactive data analysis. The research results show that there are weaknesses in the dimensions processes which results in implementation not going well. Validation and Verification Activities for Prospective beneficiaries are carried out by system without going through field verification by facilitator. The beneficiaries Verification activity was not carried out due to the matching of social assistance data with population data and education data. The activity of updating beneficiaries data did not run optimally due to a poor coordination process between facilitator and the Village Government. However, an assessment of the quality of policy output shows high performance. Of the seven aspects reviewed, there were two aspects that showed they were ineffective, namely the bias aspect and the program coverage aspect. The validity of data on beneficiaries is not yet completely good because there are still beneficiaries who are not eligible to receive social assistance, resulting in bias. Program coverage is still minimal in terms of the number of beneficiaries, only around 20% of the existing poor families